Household Firewood Consumption and its Dynamics in Kalisizo Sub-County, Central Uganda - Agea, Jacob G.; Kirangwa, Denis; Waiswa, Daniel; Okia, Clement A. (My University, 2010)
This study examined household firewood consumption and its dynamics in Kalisizo sub-county of Rakai district, central Uganda. Fifty households were conveniently selected and administered with semi-structured questionnaires to determine the preferred tree/shrub species for firewood and the socio-economic dynamic of firewood consumption in the households. Direct measurements were made to quantify the daily amount of firewood consumed by the households. Questionnaire responses were analyzed using Statistical Package for Social Sciences (SPSS), while the volume of firewood consumed per household was computed using the formula, V = (pd2l)/4. Findings indicated a very strong positive correlation (R2 = 0.919) between a household family sizes and the volume of firewood consumed per day. On average, a household with a family size of about seven persons consumed 1.56 m3 of firewood per year. The most preferred tree and shrub species for firewood were Sesbania sesban (85%), Eucalyptus (83%), Calliandra calothyrsus (73%), Ricinus communis (68%), and Ficus natalensis (63%). Most of the species were reported to have good combustion characteristics. Firewood collectors covered 8 to 12 km and spent 4 to 6 hours daily to gather firewood, and on average many households collected 4 to 6 headloads of firewood per week. Most people preferred smaller diameter (13–56 mm) pieces of firewood, as they are easy to cut and transport as headloads. All the households interviewed said they occasionally buy firewood especially during rainy seasons and most (92%) of them spend up to UGX 200,000 (US $ 100) per year on firewood. Ninety percent of households made two fires (traditional three-stone fire) per day and 80% prepared two meals per day. There is a need for continued sensitization of household members about fire management in traditional three-stone fire cooking stoves to reduce firewood consumption and waste. Studies have shown that efficiency of a three-stone fire cooking stoves can be quite high if the fire is closely tended and managed. Use of energy saving stoves should also be promoted to save the already scarce firewood. There is also a need for continued encouragement of households to establish their own woodlots in order to reduce the burden of firewood collection on women and children. Lastly, there is a need to quantify opportunity costs foregone by household members involved in firewood collection to give a better picture of the overall dynamic of firewood in rural household economies.
Keywords: Fuelwood; woodfuel; biomass energy; cooking; tree preferences